THE INFLUENCE OF DIVIDEND PAYOUT RATIO AND FREE CASH FLOW TO DEBT TO EQUITY RATIO - Hapsari, Yurizki Wida; Isharijadi, Isharijadi; Widhianningrum, Purweni (Jurnal Dinamika Akuntansi, 2016)
This study aimed to analyze the effect of dividend payout ratio and free cash flow to the debt to equity at the manufacturing companies which listed in the Indonesia Stock Exchange. The population of this study is manufacturing companies which listed in Indonesia Stock Exchange during the year 2010, 2011, 2012, and 2013 a number of 128 companies. Purposive sampling is used for sampling technique, as many as 33 companies. Data analytical technique in the study is multiple linear regression analysis. The results of this study proved that the dividend payout ratio had significant negative effect on the debt to equity. It showed that the dividend payments appeared as a substitute for debt in the capital structure at the company. Free cash flow positively and significantly influenced debt to equity. It was due to the investment in working capital of the company was greater than the companys operating cash flow.